Determinação in situ de metilmercúrio e mercúrio (II) em sistemas aquáticos nas proximidades de refinarias de petróleo, utilizando a técnica difusão em filmes finos por gradiente de concentração (DGT) - Tafurt Cardona, Makenly [UNESP] (2015)
An in situ method for selective determination of methylmercury (MeHg) was developed in this work by using the diffusive gradients in thin films (DGT) technique. This method was used together with an already evaluated DGT method, based on the use of P81 cationic membrane as binder for determination of mercury (II). To determine MeHg species, it was used a binder disk of Saccharomyces cerevisiae (yeast) - 20% (w / v) - immobilized on agarose 3%, polyacrylamide diffusive layers (S + P) and acetate of cellulose as a filter membrane. The P81 cationic membrane and the diffusion agarose gel (P81 + A) were used for the determination of mercury (II). The DGT devices assembled with the previously described layers were deployed in solutions prepared in laboratory, with known concentrations of MeHg (and / or Hg2+).The average MeHg diffusion coefficient obtained for polyacrylamide equals to 7.03 ± 0.77 x 10-6 cm2 s-1 at 23 °C. It was evaluated the main parameters that affect the technical performance: pH (3.5 - 8, 5) and ionic strength (I) (0.0005 mol L-1 to 0.1 mol L-1 NaCl). The analyte recoveries obtained for the pH range studied (84 - 98%) and I (84 - 105%) indicated that the method can be used in aquatic systems which meet these conditions. The effect of interference due to simultaneous presence of ions was also evaluated. Mn, Cu, Zn, Fe (II) did not affect the retention of MeHg by the binder (70 - 87% recoveries). However, the binder layer was less tolerable to presence of Pb and Cd, noticiable by lower recoveries of 62 ± 5% and 54 ± 6%, respectively. The developed method was applied in situ in Rio Negro (Manaus-AM), nearby the oil refinery Isaac Sabbá (Reman). The average concentrations of MeHg and Hg (II) were determined and the results obtained by DGT on site were (< 0,025 μgL-1) and (< 0,085 μgL-1), respectively